Impact of the Global COVID-19 Pandemic on the Incidence, Presentation, and Management of Pediatric Appendicitis: Lessons Learned from the First Wave - Saalabian, Kerstin; Rolle, Udo; Friedmacher, Florian (European Journal of Pediatric Surgery, 2021)
The fast-evolving nature of the coronavirus disease 2019 (COVID-19) pandemic has led to unprecedented clinical, logistical, and socioeconomical challenges for health-care systems worldwide. While several studies have analyzed the impact on the presentation and management of acute appendicitis (AA) in the adult population, there is a relative paucity of similar research in pediatric patients with AA. To date, there is some evidence that the incidence of simple AA in children may have decreased during the first lockdown period in spring 2020, whereas the number of complicated AA cases remained unchanged or increased slightly. Despite a worrying trend toward delayed presentation, most pediatric patients with AA were treated expediently during this time with comparable outcomes to previous years. Hospitals must consider their individual capacity and medical resources when choosing between operative and non-operative management of children with AA. Testing for severe acute respiratory syndrome coronavirus type 2 is imperative in all pediatric patients presenting with fever and acute abdominal pain with diarrhea or vomiting, to differentiate between multisystem inflammatory syndrome and AA, thus avoiding unnecessary surgery. During the further extension of the COVID-19 crisis, parents should be encouraged to seek medical care with their children early in order that the appropriate treatment for AA can be undertaken in a timely fashion.
Keywords: appendicitis; child; pediatric; coronavirus; COVID-19; SARS-CoV-2; MIS-C; PIMS-TS